2022
DOI: 10.3389/fcvm.2022.870378
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between endovascular aneurysm repair-selected and endovascular aneurysm repair-only strategies for the management of ruptured abdominal aortic aneurysms: An 11-year experience at a Chinese tertiary hospital

Abstract: ObjectivesThe aim of this study was to review our management experience of ruptured abdominal aortic aneurysms (RAAAs) using an endovascular aneurysm repair (EVAR)-only strategy, and discuss the feasibility of this strategy.Materials and methodsA retrospective analysis of clinical data was performed in patients with RAAAs from January 2009 to October 2020. Our strategy toward operative treatment for RAAAs evolved from an EVAR-selected (from January 2009 to April 2014) to an EVAR-only (from May 2014 to October … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Recently, the use of EVAR for managing rAAA has gained widespread recognition, thanks to technological advancements and updates in endovascular stents. Studies have demonstrated that EVAR can significantly reduce perioperative mortality and 5-year mortality in rAAA cases ( 4 , 11 ). The choice of endograft is a pivotal factor in the success of EVAR treatment ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the use of EVAR for managing rAAA has gained widespread recognition, thanks to technological advancements and updates in endovascular stents. Studies have demonstrated that EVAR can significantly reduce perioperative mortality and 5-year mortality in rAAA cases ( 4 , 11 ). The choice of endograft is a pivotal factor in the success of EVAR treatment ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the primary therapeutic approaches for rAAA comprise open surgical repair (OSR) and endovascular repair of abdominal aortic aneurysm (EVAR). Over the last decade, continuous technological advancements and device updates have led to a deeper comprehension of EVAR among medical practitioners ( 4 ). The utilization rate of EVAR in elective abdominal aortic aneurysm repair has increased from 54% in 2009 to 68% in 2017, surpassing OSR ( 5 ).…”
Section: Introductionmentioning
confidence: 99%